BIM-based File Synchronization and Permission Management System for Architectural Design Collaboration. Issue 3 (1st September 2017) - Kim, Mikyoung; Ji, Seungyeul; Jun, Hanjong
Abstract : In building information modelling (BIM), the amount of information increases and architectural design processes become more complex as projects expand. This is because while a collaboration environment is important for smooth communication among experts, this has not been realized because of unclassified file synchronization and permission settings among team members. Therefore, this study aims to support cooperation in BIM modelling projects by synchronizing BIM data from different computers and rendering BIM project management easier by providing a BIM model viewer and data through the Web. The proposed technology, which is a construction project-type, purpose-tailored browsing technology, provides BIM information related to construction environments and planning processes only to the relevant experts.